2019
DOI: 10.1002/aelm.201901217
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Stimulated Artificial Synapses Based on 2D Organic Field‐Effect Transistors

Abstract: the working principles of the brain, which may offer a new alternative paradigm for next-generation computation systems toward artificial intelligence. [3-8] In the nervous system, the transmission of information between neurons is usually performed in the chemical form of releasing neurotransmitters or in the electrical form of spikes, which is achieved through synapses. The ability of synapse to strengthen or weaken its connection strength between two neurons over time provides the physiological basis for sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 56 publications
2
108
0
1
Order By: Relevance
“…With an accompanying increasing research in 2D materials, a number of research groups have reported works utilizing graphene and other 2D materials in volatile and nonvolatile memory . Arnold et al reported a synaptic device through engineering of hysteresis in MoS 2 transistors to mimic the key functions in a chemical synapse .…”
Section: D Materials and Heterostructure‐based Synaptic Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…With an accompanying increasing research in 2D materials, a number of research groups have reported works utilizing graphene and other 2D materials in volatile and nonvolatile memory . Arnold et al reported a synaptic device through engineering of hysteresis in MoS 2 transistors to mimic the key functions in a chemical synapse .…”
Section: D Materials and Heterostructure‐based Synaptic Devicesmentioning
confidence: 99%
“…Together with the inorganic 2D materials, 2D organic layers have attracted the attention of researchers because the solution‐based process and flexibility in 2D organic layer materials enable low fabrication cost for large‐area production. In particular, 2D organic molecules modulate the response to external signals, providing a potential platform for realizing sensory synapses in multidimensions …”
Section: Introductionmentioning
confidence: 99%
“…By comparing the devices with and without interfacial layer, it could be found that the interfacial charge trapping effect was the key to mimic the biological synapse. [ 30 ] Synaptic weight was an important parameter in artificial synapses, the change of which represented the plasticity of synapses after external operation (electrical pulse or light pulse) was applied. The change of synaptic weight can be expressed as the following formulation ΔSW=I1I0I0×100% where I was the synaptic weight, I 0 was the initial synaptic weight, and I 1 was the synaptic weight after external operation was applied.…”
Section: Interface Engineering In Synaptic Applicationsmentioning
confidence: 99%
“…[4][5][6] Recently, in order to enrich the variety of devices, some new materials including nanoparticles, [7] polymer, [8] ferroelectric, [9] organic small molecules, [10] 2D materials, [11] and hybrid composites [12] were developed and applied in three-terminal organic memory devices, contributing to the development of three new kinds of OFET memory devices, electrodes/semiconductor layer; therefore, the interface plays an important role in these devices. [30] In this review, we focus on the interface engineering in three-terminal organic memory devices (Figure 1). First, the factors affecting the electrical properties will be examined from the perspective of interface, including four main factors morphology, surface diploes, adhesion, and surface energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation